Towards a Theory for the Interpretation of Material Remains in Archaeology: The Bronze Age Anthropomorphic Figurines from Cyprus - Orphanides, Andreas Gregory (1986)
Ph.D. Dissertation; Order No. DA8614606; cf. DissAbstr 47/04 (October 1986) 1380-A.